2022
DOI: 10.1007/s10340-022-01484-6
|View full text |Cite|
|
Sign up to set email alerts
|

Odor learning improves efficacy of egg parasitoids as biocontrol agents against Tuta absoluta

Abstract: Trichogramma spp. (Hymenoptera: Trichogrammatidae) are generalist egg parasitoids widely used as biological control agents, yet with limited efficacy against Tuta absoluta (Meyrick; Lepidoptera: Gelechiidae), a key pest of tomato. Olfactory cues related to the host-plant complex influence the searching behavior in parasitoids. Studies have shown that female Trichogramma spp. can learn odor cues affecting their preference. We assessed if learning increases the response to tomato odor and whether it improves the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Our results showed that the multiplication of this parasitoid by successive generations in the target host may affect its behavior, possibly leading to a greater potential for parasitism of the target host in the field. It is also worth considering that learning can also occur in the adult stage of the parasitoid (Keaton & Woods, 2016; Vargas et al., 2017; Giustina et al., 2022; Gonthier et al., 2022). Thus, because the response to the extracts was similar to that observed in eggs, the presence of these odors after parasitoid emergence (imaginal conditioning) could be an alternative for T. pretiosum learning before release, possibly optimizing its search and parasitism process in S. frugiperda eggs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the multiplication of this parasitoid by successive generations in the target host may affect its behavior, possibly leading to a greater potential for parasitism of the target host in the field. It is also worth considering that learning can also occur in the adult stage of the parasitoid (Keaton & Woods, 2016; Vargas et al., 2017; Giustina et al., 2022; Gonthier et al., 2022). Thus, because the response to the extracts was similar to that observed in eggs, the presence of these odors after parasitoid emergence (imaginal conditioning) could be an alternative for T. pretiosum learning before release, possibly optimizing its search and parasitism process in S. frugiperda eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the host in which parasitoids develop, Gonthier et al. (2022) observed that rearing Trichogramma achaeae Nagaraja & Nagarkatti, currently used for biological control of Tuta absoluta (Meyrick) in Europe (Desneux et al., 2021), strongly increased the arrestment time on eggs in this host. Despite the importance of T. pretiosum in the biological control of S. frugiperda , the effect on the foraging behavior and the biotic potential of females after successive generations in S. frugiperda eggs is not known.…”
Section: Introductionmentioning
confidence: 99%